Early-onset breast cancer in a woman with a germline mobile element insertion resulting in BRCA2 disruption: a case report - Deuitch, Natalie (Hum Genome Var, 2020)
Mobile element insertions (MEIs) contribute to genomic diversity, but they can be responsible for human disease in some cases. Initial clinical testing (BRCA1, BRCA2 and PALB2) in a 40-year-old female with unilateral breast cancer did not detect any pathogenic variants. Subsequent reanalysis for MEIs detected a novel likely pathogenic insertion of the retrotransposon element (RE) c.7894_7895insSVA in BRCA2. This case highlights the importance of bioinformatic pipeline optimization for the detection of MEIs in genes associated with hereditary cancer, as early detection can significantly impact clinical management.